Antibiotic resistance trends of ESKAPE pathogens in Kwazulu-Natal, South Africa: A five-year retrospective analysis - Ramsamy, Y; Essack, SY; Sartorius, B; Patel, M; Mlisana, KP (AOSIS, 2018)
Background: To combat antimicrobial resistance, the World Health Organization developed a global priority pathogen list of antibiotic-resistant bacteria for prioritisation of research and development of new, effective antibiotics.